Pengaruh Model Pembelajaran Kooperatif Tipe CIRC (Cooperative Integrated Reading And Composition) Terhadap Keterampilan Membaca Teks Persuasi Siswa Kelas VIII SMP Negeri 3 Pariaman - Indriani Hasibuan; Afnita Afnita (Pusat Riset dan Inovasi Nasional, 2023)
This article was written to explain the influence of the CIRC (Cooperative Integrated Reading and Composition) cooperative learning model on the reading comprehension skills of persuasive texts for class VIII students of SMP Negeri 3 Pariaman. The research data is the score of the objective test results before using this type of cooperative learning model with the score after getting treatment using this learning model. Based on the results of the research, it can be concluded that there are three results that become findings, namely as follows. First, the reading comprehension skills of persuasive texts before using the cooperative learning model type CIRC (Cooperative Integrated Reading and Composition) class VIII students of SMP Negeri 3 Pariaman are in the